2023
DOI: 10.1002/ajh.27177
|View full text |Cite
|
Sign up to set email alerts
|

Immunoglobulin light chain amyloidosis: 2024 update on diagnosis, prognosis, and treatment

Morie A. Gertz

Abstract: Disease OverviewImmunoglobulin light chain amyloidosis is a clonal, nonproliferative plasma cell disorder in which fragments of immunoglobulin light or heavy chain are deposited in tissues. Clinical features depend on organs involved but can include heart failure with preserved ejection fraction, nephrotic syndrome, hepatic dysfunction, peripheral/autonomic neuropathy, and “atypical smoldering multiple myeloma or MGUS.”DiagnosisTissue biopsy stained with Congo red demonstrating amyloid deposits with apple‐gree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 184 publications
(228 reference statements)
0
2
0
Order By: Relevance
“…The prognosis assessment in AL amyloidosis is a rapidly changing field. Stage is considered the most important predictor of outcome [39]. However, the use of two different staging systems has potential for stage to be confounder [40].…”
Section: Discussionmentioning
confidence: 99%
“…The prognosis assessment in AL amyloidosis is a rapidly changing field. Stage is considered the most important predictor of outcome [39]. However, the use of two different staging systems has potential for stage to be confounder [40].…”
Section: Discussionmentioning
confidence: 99%
“…Primary causes of dysautonomia include pure atrophy, multisystem atrophy, Parkinson's disease, and Lewy body dementia [25]. Secondary dysautonomia is caused by diabetes [26], amyloidosis [27], uremia [28], metabolic syndrome [29], heart failure [30], or other cardiovascular and non-cardiovascular diseases [31,32], as well as drugs causing sympathetic inhibition (e.g., antipsychotics via α1 and d2, antidepressants via antimuscarinic activity), vasodilation, cardio-inhibitory effects, or volume depletion (diuretics) [33]. Both acute SARS-CoV-2 infection and its post-acute sequelae are characterized by autonomic dysfunction and an altered mechanism of blood pressure variability and may manifest as syncope [34,35].…”
Section: The Baroreceptor Reflexmentioning
confidence: 99%
“…The immediate goal for therapy in patients with systemic immunoglobulin light chain amyloidosis (AL) is to swiftly achieve at least a hematologic very good partial response (VGPR), given the consistently improved organ responses and survival with achievement of deep hematologic responses [ 1 3 ]. The phase III ANDROMEDA trial demonstrated that the addition of daratumumab to bortezomib, cyclophosphamide, and dexamethasone (D-VCd) resulted in significantly higher hematologic CR (53%) and VGPR rates (78%) compared to VCd in previously untreated patients [ 4 ].…”
mentioning
confidence: 99%